Seasonal dynamic of macroalgae in intertidal pools formed by beds of Crassostrea gigas (Mollusca, Bivalvia) on the north Patagonian Atlantic coast - Croce, Maria Emilia (2012)
Intertidal pools represent restricted habitats for macroalgal assemblages, and their structure is determined by physical and biotic factors. The establishment of the exotic oyster Crassostrea gigas on the north Patagonian Atlantic coast led to the formation of intertidal pools; these provide habitats for macroalgal settlement. We aimed to determine the composition, distribution and abundance of the macroalgal assemblage inhabiting these pools, and to establish the structuring variables. Several biotic and abiotic variables were evaluated in 36 pools in winter and summer. Correlations were calculated and permutation analysis of variance and constrained redundancy analysis were conducted to determine the structuring variables. Unlike other Patagonian coasts, richness was low and pools were characterized by a dominance of red algae. Richness was higher in winter, while diversity was lower because of the dominance of Polysiphonia abscissa, which had the highest percentage of occurrence. Temperature was a putative factor determining seasonal richness and diversity. Elevation and surface area of the pools were structuring factors for assemblage biomass. We demonstrated distinct assemblage dynamics. Polysiphonia abscissa developed large populations in winter, which declined towards the summer, while Gelidium maggsiae and Gelidiella calcicola formed dense turfs during summer stress.